Termites: the good, the bad and the ugly - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Termites of many different kinds are found throughout the tropics. Little is known about their impact on agriculture, even though there have been many studies of the social organization of termites within their colonies. What influence do termites...